2008
DOI: 10.1097/pcc.0b013e31816c7082
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral edema in diabetic ketoacidosis

Abstract: The causes and mechanisms of CEDKA are unknown. CEDKA may be due as much to individual biological variance as to severity of underlying metabolic derangement of the child's state and/or treatment risk factors. Treatment recommendations for CEDKA and diabetic ketoacidosis are made taking into consideration possible mechanisms and risk factors but are intended as general guidelines only in view of the absence of conclusive evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 179 publications
(177 reference statements)
2
62
1
2
Order By: Relevance
“…Rosenbloom reported that 8-10% of instances of clinically apparent generalized cerebral oedema will be associated with localized basilar oedema 7 . The reasons for this different type of oedema may be related to DKA being related to more vasogenic (blood brain barrier) than cytotoxic oedema 5 . Further, recent studies show that in DKA, there are regional increases in the blood-brain-barrier permeability ratio 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosenbloom reported that 8-10% of instances of clinically apparent generalized cerebral oedema will be associated with localized basilar oedema 7 . The reasons for this different type of oedema may be related to DKA being related to more vasogenic (blood brain barrier) than cytotoxic oedema 5 . Further, recent studies show that in DKA, there are regional increases in the blood-brain-barrier permeability ratio 12 .…”
Section: Discussionmentioning
confidence: 99%
“…One important challenge in DKA is the vulnerability to intracerebral complications and the subsequent neurological deterioration. The recognized causes for neurological deterioration are cerebral oedema, cerebral infection, cerebrovascular accidents and basilar oedema 5,6 . Among these, cerebral oedema is the foremost significant contributor to mortality and morbidity in children with DKA 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that pathophysiology of brain edema in DKA is more likely of vasogenic than cellular nature, caused by blood-brain barrier disruption with increased vascular permeability and brain inflammatory response 9,10 . Although the very treatment of DKA is considered to be the main culprit for the development of brain edema, the nature of the pathophysiological processes in DKA is accountable for neurological complications of this condition: accumulation of intracellular osmoles, elevated levels of vasopressin, the increase in the concentration of atrial natriuretic factor 24 hours after the start of therapy, hypoxia and ischemia, abnormality in numbers and functions of aquaporin channels 10 . The most important risk factors for the development of brain edema in DKA are: rapid correction of electrolyte disturbances, application of bicarbonates, intensive hyperventilation (resulting in too low pCO 2 ) and a younger age 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the very treatment of DKA is considered to be the main culprit for the development of brain edema, the nature of the pathophysiological processes in DKA is accountable for neurological complications of this condition: accumulation of intracellular osmoles, elevated levels of vasopressin, the increase in the concentration of atrial natriuretic factor 24 hours after the start of therapy, hypoxia and ischemia, abnormality in numbers and functions of aquaporin channels 10 . The most important risk factors for the development of brain edema in DKA are: rapid correction of electrolyte disturbances, application of bicarbonates, intensive hyperventilation (resulting in too low pCO 2 ) and a younger age 10,11 . Brain edema is the most serious complication of DKA, with a high rate of mortality (21-25%) and morbidity (30-40%), so understanding pathophysiology, prevention and treatment of cerebral edema is paramount in improving the outcome of DKA 2,4 .…”
Section: Discussionmentioning
confidence: 99%
“…Les complications neurologiques du diabète surviennent le plus souvent lors de la découverte de celui-ci : coma acidocétosique avec risque d'oedème cérébral qui peut survenir dans les 48 premières heures de prise en charge (favorisé par le jeune âge, l'administration de bicarbonates de sodium en bolus, des volumes de perfusion trop élevés ou une chute trop rapide de l'osmolarité plasmatique dont les marqueurs périphériques sont la glycémie et la natrémie corrigée) [36] ou coma hyperosmolaire se rapprochant de celui de l'adulte [37]. L'objectif initial sera la restauration de la volémie par la réalisation d'un ou de plusieurs remplissages vasculaires au sérum physiologique, puis la réhydratation prudente avec insulinothérapie pour correction lente de l'osmolarité plasmatique.…”
Section: Troubles Métaboliquesunclassified